Faktor-faktor penyebab rendahnya Penggunaan Kontrasepsi Jangka Panjang (MKJP) di Wilayah Kerja Puskesmas Betung Kecamatan Lubuk Keliat Kabupaten Ogan Ilir Tahun 2022 - Alawiyah, Alawiyah; Asiyah, siti; Anggraini, arie (NHM PRESS, 2023)
According to data from the World Health Organization (WHO) more than 100 million couples use effective contraceptives, worldwide with 75% of hormonal contraceptive users and 25% using non-hormonal contraceptives. Determinant factors influencing the use of long-term contraceptive methods (MKJP) were the age of PUS, parity, spacing of pregnancies, husband's support, previous family planning history, education, employment, economic status, family planning services and staff, KIE, family planning, acceptor's physical condition, and knowledge about MKJP. This study aimed to determine the relationship between age, education, and employment with low use of long-term contraception (MKJP) in the working area of the Betung Health Center, LubukKeliat District, in 2022. The research design used an analytical survey with a cross-sectional approach. The population in this study were all active family planning acceptors recorded in the medical records at the Betung Health Center, LubukKeliat District, in 2022 totaling 1773 respondents. The sampling technique in this study was carried out by means of systematic random sampling with a total sample of 95 respondents. Data collection used a checklist sheet. Data analysis used univariate analysis and bivariate analysis using the chi-square test. The results of the study showed that there was a relationship between age (p-value = 0.026), education (p-value = 0.035), and occupation (p-value = 0.025) to the low use of long-term contraception (MKJP) in the Betung Health Center work area, LubukKeliat District in 2022. It is recommended that health workers provide counseling and outreach to the community, especially women of childbearing age, regarding MKJP contraception to increase the use of MKJP in their working areas.